2022
DOI: 10.3390/nu14112307
|View full text |Cite
|
Sign up to set email alerts
|

Cornus mas L. Increases Glucose Uptake and the Expression of PPARG in Insulin-Resistant Adipocytes

Abstract: Cornus mas L., also known as cornelian cherry (CM), is a species that has long been cultivated in many different countries. In numerous scientific reports, cornelian cherry is used to treat numerous diseases and conditions. The presented study evaluated the effect of red and yellow Cornus mas L. extract on insulin sensitivity in adipocytes. 3T3-L1 fibroblasts as well as human SAT-derived and VAT-derived adipocytes were differentiated in vitro, and insulin resistance was induced using palmitic acid (16:0). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, dogwood is a rich source of minerals such as calcium, potassium, phosphorus, sodium, magnesium, iron, zinc and copper [21]. The composition of biologically active substances varies depending on the part of the plant [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dogwood is a rich source of minerals such as calcium, potassium, phosphorus, sodium, magnesium, iron, zinc and copper [21]. The composition of biologically active substances varies depending on the part of the plant [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an upregulation of PPAR-γ was observed with the treatment with the TPDM6315 extracts (AE100 and EE10) and TGZ. These findings revealed a potential mechanism for TPDM6315, with a possible function of the PPAR-γ agonist that could be used to treat insulin resistance in type 2 diabetes [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPI network and GO/KEGG pathway enrichment analysis showed that AO toxic compounds mainly targeted PPARG and TNF and regulated the lipid and atherosclerosis signaling pathway. PPARG, also known as peroxisome proliferator-activated receptor gamma, is a nuclear receptor binding peroxisome proliferator that regulates adipocyte differentiation and controls the peroxisomal beta-oxidation pathway of fatty acids ( Małodobra-Mazur et al, 2022 ). Tumor necrosis factor (TNF) is mainly secreted by macrophages and can induce insulin resistance through inhibition of Insulin receptor substrate 1 (IRS1), tyrosine phosphorylation and G kinase-anchoring protein 1 (GKAP42) degradation in adipocytes ( Ando et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%